1994
DOI: 10.1093/nar/22.20.4307
|View full text |Cite
|
Sign up to set email alerts
|

Antisense oligonucleotides in solution or encapsulated in immunoliposomes inhibit replication of HIV-1 by several different mechanisms

Abstract: Phosphodiester and phosphorothioate oligonucleotides in a and , configurations directed against the initiation codon region of the HIV-1 rev gene were evaluated for their ability to inhibit HIV-1 replication in acutely and chronically infected human CEM cells. Encapsulation in antibody-targeted liposomes (immunoliposomes) permitted intracellular delivery and distinction between oligonucleotide-mediated inhibition of viral entry and intracellular effects on viral RNA. Our results are consistent with four mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(31 citation statements)
references
References 48 publications
2
29
0
Order By: Relevance
“…were not due to a significant variation of the hybridization efficiency of oligonucleotides to the RNA: the melting temperatures ranged from 55 to 61°C for the three 17~fl oligonucleotides and their unmodified (17fl17) and fully modified alpha analogues (170~17) ( Table 1), in agreement with previous results [15,16]. Furthermore, the 3'-3' link between the alpha and the beta portions did not significantly destabilize the hybrids [13].…”
Section: Cleavage Of An Rna Target By the Rt Rnase Hsupporting
confidence: 89%
“…were not due to a significant variation of the hybridization efficiency of oligonucleotides to the RNA: the melting temperatures ranged from 55 to 61°C for the three 17~fl oligonucleotides and their unmodified (17fl17) and fully modified alpha analogues (170~17) ( Table 1), in agreement with previous results [15,16]. Furthermore, the 3'-3' link between the alpha and the beta portions did not significantly destabilize the hybrids [13].…”
Section: Cleavage Of An Rna Target By the Rt Rnase Hsupporting
confidence: 89%
“…This mechanism is conventionally termed in the literature and in this report as "antisense." It is well established that [26][27][28][29][30][31][32] antisense ODNs might have, in addition, activity that is related to a "non-antisense" effect (ie, not related to an antisense effect) as we have referred to it here. This non-antisense effect can be due to multiple mechanisms comprising those originating from the activity of a specific ODN sequence (termed here as a "sequence-specific" effect) and those originating from the activity of an ODN that is not specific to a particular sequence (termed here as a "non-sequence-specific" effect).…”
Section: Experimental Protocol Designmentioning
confidence: 99%
“…It is possible that release of ILs, such as INF-gamma, tumor necrosis factor , or IL-12, may be involved in anti-HIV activity in the assays used in this study, thus contributing to the random ODNs' high activity. PS-ODNs have been shown to inhibit the replication of HIV-1 in vitro by both sequencespecific 19,29,37,38 and non-sequence-specific [29][30][31][32] processes depending on the cell culture model employed. In acute-infection models, non-antisense inhibition of PS-ODNs has been well documented 1 and might occur, because of interference with virus adsorption, by binding to the CD4 receptor or the V3 loop of viral gp120, [39][40][41] or with reverse transcription.…”
Section: Previously Described Non-specific Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, phosphorothioate ODNs have also been shown to inhibit HIV-1 infection in a non-sequence-dependent manner particularly due to an interaction with the HIV-1 envelope protein and its cellular receptor, CD4 [6][7][8][9]. Accordingly, several studies have reported difficulties or limitations in demonstrating sequence specific inhibition of HIV-1 by fully modified phosphorothioate ODNs added to the culture medium of acutely infected cells [10][11][12][13][14]. One important reason for using phosphorothioate ODNs in antisense studies has been their resistance to nucleolytic degradation compared to unmodified ODNs [15][16][17].…”
Section: Introductionmentioning
confidence: 99%